Automatic measurement of LV wall thickness from 2D cardiac echocardiography. (4th February 2022) - Fernandes, JF; Loncaric, F; Marciniak, M; Gilbert, A; Smistad, E; Lovstakken, L; Mcleod, K; Sitges, M; Lamata, P
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – EU funding. Main funding source(s): PIC from European Union"s Horizon 2020 Marie Skłodowska-Curie Actions ITN Background: The wall thickness of the left ventricle (LV) is an important parameter in the diagnosis of hypertension and more specifically in hypertrophic cardiomyopathy. A user-dependent manual assessment of distances on 2D echocardiographic images is the current clinical gold-standard. Purpose: The automation of LV wall thickness measurements in 2D echocardiography in order to improve robustness and reduce time of clinical reports where wall thickness is required, such as hypertrophy and the presence of Basal Septal Hypertrophy (BSH)(1). Methods: A dataset of 4-chamber (4CH) echocardiograms on 118 patients with a diagnosis of hypertension (2) is used for this study. The images were segmented automatically (3) extracting the blood pool and the myocardium. Based on the curvature of the complete myocardial contour, the valve annular regions are removed leaving the endocardial and the epicardial walls as independent structures. The wall thickness along the myocardium is calculated as the distance from each endocardial border pixel to the closest epicardial point  (see Figure 1). A high pass gaussian filter was applied to remove high frequency noise. Ultimately, the basal-to-mid septal wall thickness ratio that defines BSH (ratio ≥ 1.4) was computed as the maximal of basal-septal segment divided by minimum of mid-septal segment. In order to validate the method for BSH detection, the wall thickness septal ratio was carefully measured by a clinical expert following the guidelines (2). The statistical agreement was accessed via linear correlation and Bland-Altman analysis. Results: The automatic assessment of LV wall thickness along the myocardium is feasible in 2D echocardiography. The septal ratio showed an excellent agreement with manual measurements (R2 = 0.94, bias=-0.01, see Figure 2), leading to a detection of BSH in n = 19 vs the n = 18 detected manually (1 false-negative and 2 false-positives). In comparison to the intra and inter-observer variabilities of 12% and 42% respectively in the manual measurement (4), the automatic method had no variability for a given image acquisition. Conclusions: The automatic measurement of myocardial wall thickness from a 2D echocardiographic images is accurate and reproducible. The implementation of the methodology in clinical practise has the potential to improve and automate the assessment of hypertrophic cardiac conditions.